2002
DOI: 10.1111/1468-2435.00186
|View full text |Cite
|
Sign up to set email alerts
|

Adopted Children in the Labour Market — Discrimination or Unobserved Characteristics?

Abstract: Detecting ethnic discrimination in the labour market using individual data is aggravated by individual ethnic-specific characteristics that are unobserved by the researcher.In an attempt to estimate the effect of skin colour on the probability of being employed (vs, unemployed), the labour market success of foreign-born adopted individuals is compared with that of natives. Specifically, the unexplained differences in the probability of being employed between natives and adoptees is investigated using Oaxaca-Bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 6 publications
1
16
0
3
Order By: Relevance
“…The results indicate that, as expected, segregation at the workplace level is lower for GN immigrants than for GS immigrants. This is indirect evidence in support of previous studies that show that having a nonwhite skin color is a powerful factor explaining difficulties to integrate in the Swedish labor market (Hedberg and Tammaru 2013;Rooth 2002;Rydgren 2004). This finding is usually interpreted as evidence of discrimination by natives.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results indicate that, as expected, segregation at the workplace level is lower for GN immigrants than for GS immigrants. This is indirect evidence in support of previous studies that show that having a nonwhite skin color is a powerful factor explaining difficulties to integrate in the Swedish labor market (Hedberg and Tammaru 2013;Rooth 2002;Rydgren 2004). This finding is usually interpreted as evidence of discrimination by natives.…”
Section: Discussionsupporting
confidence: 87%
“…However, residential neighborhood-based discrimination is just one aspect of the discrimination faced by immigrants seeking a job; just a mild bias in favor of members of one's own group can result in substantial discrimination of immigrants in the hiring process (Arrow 1973;Barth et al 2012;Rydgren 2004). In Sweden, a study by Rooth (2002) demonstrated that even adopted children who were born in the GS but who have been raised in Swedish native families, have attended Swedish schools, and are part of native social networks perform significantly worse in the labor market than natives. Other studies confirm that visible minorities from the GS face significant difficulties in the Swedish labor market (Attström 2007;Hedberg and Tammaru 2013).…”
Section: Discrimination Effectmentioning
confidence: 99%
“…[5][6][7] Previous studies from the US and UK have demonstrated ethnic discrimination can limit access to healthcare services among minority ethnic groups. [7][8][9][10][11] However, there is a scarcity of studies on the effects of other forms of discrimination on access to healthcare services and other determinants of health. In Sweden 12 and the US 13 racial discrimination has been associated with limited participation in the labour market and unfavourable socioeconomic circumstances.…”
mentioning
confidence: 99%
“…Other studies perform different types of more direct tests of discrimination in Sweden (for example, Rooth (2001) and Åslund and Rooth (2005)). These studies focus on the labour market outcomes of certain groups of immigrants, while we consider that attitudes may affect their migration decision as well.…”
Section: Related Researchmentioning
confidence: 99%